Neuropsychological functions among adolescents with persistent, subsyndromal and remitted attention deficit hyperactivity disorder. Issue 8 (June 2014) - Lin, Y. J.; Chen, W. J.; Gau, S. S.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Previous studies have reported mixed results on neuropsychological deficits in attention deficit hyperactivity disorder (ADHD) and only a few studies have focused on adolescents. There is also a debate about whether the executive function (EF) impairments in ADHD are primary deficits or have some contribution from the underlying non-EF processes. The aim of this study was to investigate the impairments in EF and neuropsychological function with relatively low executive demand (low-EF) in adolescents with childhood diagnosis of ADHD as a function of current ADHD status. Method Psychiatric diagnostic interviews and computerized neuropsychological tests classified into EF and low-EF tasks were completed by 435 adolescents with a childhood diagnosis of ADHD (300 adolescents classified as persistent ADHD, 109 as subsyndromal ADHD and 26 as remitted ADHD based on the current diagnosis) and 263 typically developing (TD) adolescents. Results There were significant EF (spatial working memory, spatial planning and verbal working memory) and low-EF (signal detectability, spatial span and visual recognition memory) impairments in persistent and subsyndromal ADHD. The impairments in EF were independent of low-EF despite significant moderate correlations between any two of these tasks. Adolescents with remitted ADHD showed no deficit in either EF or low-EF. Conclusions This study suggests that adolescents with persistent and subsyndromal ADHD have EF and low-EF impairments that might contribute to ADHD independently.